Sistem Jual Beli Online Dalam Perspektif Ekonomi Islam (Studi Kasus Pada Toko Jimco Sumberejo) - Eva Ruliyan; Hesti Lailani (Dinar Islamic Review, 2020)
The modern era has brought many changes in terms of buying and selling, such as utilizing the internet media so that the buying and selling process is getting easier and faster, these buying and selling transactions are known as Online Shops. Problems arise from online activities in the form of responsibility to customers, business people can commit violations that harm customers because the online buying and selling system does not bring together sellers and buyers. The formulation of the problem in this study is how the online shop buying and selling system is at the Jimco Sumberejo Store, how is the impact of online buying and selling at Jimco Sumberejo and how is the Islamic economic perspective on the implementation of the online shop buying and selling. The purpose of this study is to explain the implementation of buying and selling online shop at Jimco Sumberejo, knowing the impact of buying and selling online at Jimco Sumberejo and explaining the perspective of Islamic economics on the implementation of buying and selling online shop at Jimco Sumberejo Store. This study uses a descriptive qualitative approach. Collecting data using interviews and documentation. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results showed that the implementation of the online trading system at the Jimco Sumberejo Store utilized online social networking sites such as Facebook, Whats Apps, and Instagram. The mechanism for implementing online buying and selling is selecting, ordering (ordering), payment by transfer to an account and delivery of goods through Pos Indonesia and other delivery services. The sharia economic perspective on the implementation of buying and selling online shops at Jimco Sumberejo is allowed and legal, because buying and selling transactions that meet sharia economic principles, namely fulfilling sharia economic principles, namely fulfilling the principle of monotheism, the principle of justice ('Adl), the principle of nubuwwah (prophecy), the principle of help -helping (Ta'awun), the principle of prohibiting buying and selling contains gharar, the principle of prohibiting buying and selling contains zhalim, the principle of prohibiting buying and selling contains maysir and the principle of prohibiting the sale and purchase of illicit goods.